Publication, Compensation, and the Public Affairs Discount: Does Gender Play a Role? - Lori L. Taylor; Kalena E. Cortes; Travis C. Hearn (Institute of Labor Economics (IZA), 2019)
This paper presents on three new styled facts: first, schools of public affairs hire many economists; second, those economists are disproportionately female; and third, salaries in schools of public affairs are, on average, lower than salaries in mainline departments of economics. We seek to understand the linkage, if any, among these facts. We assembled a unique database of over 2,150 faculty salary profiles from the top 50 Schools of Public Affairs in the United States as well as the corresponding Economics and Political Science departments. For each faculty member we obtained salary data to analyze the relationship between scholarly discipline, department placement, gender, and annual salary compensation. We found substantial pay differences based on departmental affiliation, significant differences in citation records between male and female faculty in schools of public affairs, and no evidence that the public affairs discount could be explained by compositional differences with respect to gender, experience or scholarly citations.
Keywords: J01; J16; J30; J31; 330; hedonic wage models; faculty sorting; compensating differentials